University tutoring: didactic proposals in tutorial competences - Eduardo Dopico Rodríguez (Red U, 2013)
Like other educational activities subject to academic routines, tutoring function is also carried out with automatisms that are gradually becoming obsolete. The active participation of teachers who conduct researches aimed to identify these unreflective habits helps us to overcome them and design proposals for teacher training that improve the teacher-tutor profile. Tutoring at University requires an adjustment of the teaching competencies suggested in the European Higher Education Area (EHEA) to the needs of students who attends the new Degrees, B.A, M.A and Ph.D. In order to infer the meaning of the tutorial function in Higher Education and identify new teaching skills, it is necessary to research the tutorial action in the different formal educational levels (Primary, Secondary and Baccalaureate), non-formal education (training programs) and distance learning (open university). It is also analysed how tutoring is performed while describing how it is perceived by the teachers who carried it out. This process of analysis, description and interpretation is put into practice in more detail at university, through direct interviews and questionnaires among teachers and students. The results obtained make us propose strategies to make the present tutorial framework more flexible to introduce new guidelines and scenarios for teacher-student interaction and intercommunication.